Sacred Mountains and Disguising Sutras in Shaka no honji: Japanese Narratives of the Life of the Buddha - Tantisuk, Namsai (Journal of Letters, 2023)
This article is a part of the research project Reading Japanese Buddha’s Life Story: Focusing on Shaka no honji. The goal is to analyze Japanese narratives of the life of the Buddha through a case study of Shaka no honji (The Story of Sakyamuni), investigating Japanese beliefs that may be deduced from the narrative. In this article, some unique elements of Shaka no honji were investigated: sacred beings as the Buddha or Prince Siddhartha’s retinue and sacred mountain beliefs. In Shaka no honji (Honji-kei), the Lotus sutra disguised in ascetic form participated in Prince Siddhartha’s retinue. This element underlines belief that the sutra represents Buddha, so each character represents a sacred text. The disguising of the Lotus sutra matches the reproduction of similar elements from medieval Japanese Buddhist literature. In terms of belief in sacred mountains, Shaka no honji contains several mountain scenes featuring elements of sacred mountain beliefs. Ancient Japan retained traces of belief in mountains as sacred multi-space sites: the afterworld, pure land, andplaces to study to attain a purer or higher status.